Estimation of the ionic content of the groundwater Surrounding the al - Bassa landfill, Lattakia, Syria (Latakia University Journal -Basic Sciences Series, 2019)
The research included periodic physical and chemical analysis of the groundwater surrounding the waste landfill located in the area Al-Bassa in Lattakia countryside Syria, By choosing ten wells surrounding the landfill area, wells (B1®B5) are located in the current landfill, wells (B6®B10) are located in the old landfill area, where they were sampled over a year.The study included Measurement (pH), electrical conductivity (EC), turbidity (NTU) and dissolved oxygen (DO), in addition to determining the Concentrations of each), , , ).Used in this study ionic-selective electrodes (ISEs), device analysis Chromatography ionic (IC) and the Field devices to measure of the other specifications.The results showed that the values of( turbidity, conductivity, concentrations each of chloride, nitrate, phosphates and sulphates) were higher for the wells surrounding the current site than the wells surrounding the old landfill, while the dissolved oxygen values of the wells surrounding the old landfill were higher than the wells surrounding the landfill current .The highest value for chloride aions, nitrates and sulphates in winter is Estimated on the order:126.32 (mg / l) of well (B5), 268.56 (mg / l) of well (B2), 163.88 (mg / l) for well (B5), , as for phosphate the highest value was in the spring (4.69 mg / l) of well (B1).Nitrate and phosphate values for water wells have often exceeded permissible drinking water standards due to the arrival of contaminated solid waste into groundwater sources as well as rain precipitation that carries with it the residues of agricultural fertilizers and groundwater.